State-Religion Relationships in Ukraine during the Covid-19 Pandemic: Specific and Particular Features - Yevhen Kharkovshchenko; Vitalii Turenko (International Society of Philosophy and Cosmology, 2021)
This paper presents the particular functioning of state-religion relationships in Ukraine during the coronavirus pandemic. Our research proved that the Ukrainian government has developed two strategies - a restrictive strategy and a partner strategy - in dealing with religious organisations in this crisis. Restrictions were aimed at reducing coronavirus cases in the country. The partnership was created to provide mutual aid in treating the infected citizens of Ukraine. The authors have also proved that religious organisations in Ukraine found themselves in a difficult situation - between the threat of their total discontinuation and the challenges of possible transformation of their activity. Therefore, a partial limitation of church service attendance has been introduced, focusing on the fact that a religious organisation cannot waive church services since that would contradict its nature and mission. The authors have concluded that further harmonious interaction of government authorities and religious organisations in Ukraine in COVID-19 conditions depends on numerous factors: the epidemiologic situation, government decisions on the functioning of various social institutions, religious institutions in particular, and support by religious leaders of government initiatives on preventing the public spread of the disease.